Pengembangan lembar aktivitas siswa (LAS) berbasis contextual teaching and learning (CTL) pada materi prisma dan limas untuk kelas VIII Sekolah Menengah Pertama - Nefianti, Nadia; Isharyadi, Ratri; Afri, Lusi Eka (Jurnal Pendidik Indonesia, 2021)
This study aims to produce valid Student Activity Sheets (LAS) in mathematics based on Contextual Teaching and Learning (CTL) for prisms and pyramids. The research adopts a Research and Development approach consisting of three stages: defining (define), designing (design), and developing (develop). The instrument used in this study is a validation questionnaire. Through validity testing conducted with two validators and several revisions and improvements, the average score of the LAS validation results was 3.64, categorized as highly valid. Thus, the LAS developed with the Contextual Teaching and Learning (CTL) approach in this study has a very good level of validity. This research contributes significantly to developing and improving mathematics learning in the classroom. CTL-based SAS for prisms and pyramids is expected to enhance students' interest and understanding of mathematical concepts contextually, enabling them to relate their learning to everyday life situations. Moreover, the LAS development method used in this study can also be adapted to produce CTL-based student worksheets for other mathematical topics.